PEMANFAATAN TEKNOLOGI KOMPUTER PADA PELAJARAN FIQIH DI YAYASAN PESANTREN YATIM AL JIHAD SURABAYA - Naili Mufarrohah (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2021)
In the current era of globalization, it's time for us as young people to be able to use technology media properly and correctly. In addition to everyday life, the use of technology is also prioritized in terms of learning. Because at this time in providing knowledge transfer, an educator is required to use many tools or media that can facilitate students in accepting or absorbing material. If only in the learning system with the lecture method, most of the students are not interested and will tend to give a sense of boredom when in the classroom. This study aims to explain the usefulness of Information and Communication Technology at the Surabaya Al Jihad Islamic Boarding School Foundation. In this study the authors used a qualitative approach with descriptive methods. The step taken by the author is by interviewing the management in the orphaned boarding school and direct interviews with orphans who live here both male and female. The results of the research carried out here, although still in the level of infrastructure that is not fulfilled, but both caregivers and administrators have tried their best in improving and optimizing the use of technology in this case specifically on computers that have been provided in each male and female . The benefits of introducing them to technology can provide a special attraction when they are receiving lessons at home. In general, among boarding schools, learning is only limited to the teacher explaining and students note, if it is combined with the current era, this needs to be increased so that it can give different impressions and results. Even though the santri have been introduced to technology, this does not reduce or change the activities that are characteristic of pesantren, for example sorogan, Juz ‘Amma memorization deposit and of course the yellow book. Technology here is only a support for the orphaned students who are not left behind by friends in school in general. Moreover, starting this year the UNBK system has been implemented for all schools.